Hydraulic characterization of turbulent flow drippers - Fischer Filho, João A. [UNESP] (2018)
In the evaluation of hydraulic performance of four models of not self-compensating drippers was used a bench of tests with capacity for 25 drippers of each model. Each model was subjected to different pressures (p), thus determining the mean flow rate (q), the coefficient of manufacturing variation (CVf) and the characteristic equation of the dripper (q versus p). Subsequently, the Christiansen (CUC) and distribution (CUD) uniformity coefficients for 16 drippers of each evaluated model were determined under field conditions in a flat area. A completely randomized design with four repetitions and Tukey’s test were used to compare means of CUD and CUC. The four models, operating at nominal pressures, had flow rates of, respectively, 2.22; 1.30; 1.45 and 1.93 L h -1 and mean CVf of, respectively, 1.30%; 3.61%; 2.65% and 3.97%, being characterized as having excellent and average uniformity. The four models were fitted under a turbulent flow regime, with exponent values x of the characteristic equation of the dripper varying between 0.4714 and 0.5174, and R 2 determination coefficients above 99%. The values of CUC and CUD differed statistically and were, on average, higher than 90% and, in particular, the Driptech and Dripline drippers.